Heat stress risk among New York City public school kitchen workers: a quantitative exposure assessment. Issue 7 (2nd August 2020) - Ierardi, A. Michael; Pavilonis, Brian
Abstract: Despite the known human health risks associated with excessive heat exposure, particularly in occupational settings, data describing potential heat exposures in school kitchens is scarce, and no published studies to date have performed a quantitative heat exposure assessment for workers employed in this setting. The purpose of this study was to quantify the extent of heat stress in New York City public school kitchens and to assess potential risk of heat-related illness and/or acute injury. Full-shift indoor Wet Bulb Globe Temperature (WBGT) indices, as well as indoor CO2 and CO concentrations were measured for ten school kitchens. A quantitative exposure assessment for three metabolic work-rate scenarios (light, moderate, heavy) was performed in accordance with the Occupational Safety and Health Administration's (OSHA) Heat Hazard Assessment methodology. The overall mean indoor WBGT index for all ten sites was approximately 25.0 °C (77.0 °F; Standard Deviation [SD] = 2.0 °C). Regarding the estimated Action Limit, 10% of school kitchens sampled exceeded this recommended limit for the light work-rate scenario; 60% of schools exceeded this limit for the moderate work-rate scenario; and 80% of schools exceeded this limit for the heavy work-rate scenario. For the Threshold Limit Value (TLV), none of the kitchens exceeded this limit for the light or moderate work-rate scenarios; 30% of kitchens were in excess of this limit for the heavy work-rate scenario. Mean full-shift CO2 and CO air concentrations ranged from 435–911 ppm (mean = 648; SD = 158) and 0.0–3.2 ppm (mean = 0.9; SD = 0.9), respectively. The data collected in the current study suggest that kitchen staff employed in New York City public schools may be exposed to excessive indoor heat levels. Adequate work-rest schedules should be implemented for kitchen workers, in addition to other feasible engineering and administrative controls to mitigate potential risk of heat-related illness and/or acute injury.